Navigating Flexible Work Arrangements to Foster Sustainable Growth through Adaptive Innovation - Amran, Ali; Arifuddin, Arifuddin; Asril, Akmil (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
This study examines the impact of flexible work arrangements on innovation and sustainable growth in companies. Flexible working hours allow employees to set their own schedules and decide where and when they work most effectively. This allows them to spend more time at home or in the lab. Detaching the office helps increase productivity, creativity, and employee happiness. However, flexible office models and innovative product breakthroughs have become successful models, leading to success for their practitioners in every way. This study employed a mixed-methods approach, using questionnaires to collect data from 400 organizations across various industries. We also interviewed top managers in five cases. The results show that organizations that adopt flexible work significantly improve their ability to innovate. In technology, financial services, and manufacturing, organizations that work on innovative projects with at least one employee have shortened the overall time to market for new products while launching more successful products. Furthermore, improving employee quality of life is associated with higher levels of employee satisfaction, as employees enjoy their work more, which is beneficial for all parties involved. Furthermore, cyber leadership and digital collaboration technologies are key tools for the success of flexible work arrangements. The results of this study show that in terms of helping companies survive and thrive, adaptive work patterns are not only beneficial but also provide a competitive advantage for our organization over others in an already crowded market.